Buckling behaviors and ultimate strength of 6082-T6 aluminum alloy columns with square and circular hollow sections under eccentric compression – Part II: Parametric study, design provisions and reliability analysis. (October 2019) - Zhao, Yuanzheng; Zhai, Ximei; Wang, Jianhao
Abstract: The wide application of aluminum alloys has been spread in the field of civil and building engineering due to their excellent performance and advantages. The companion paper (Part I) has described the eccentrically compressive loading tests and the verification of finite element (FE) models. In this paper, a parametric study about the 6082-T6 aluminum alloy columns of square and circular hollow sections (SHS-CHS) subjected to eccentric compression was performed using the verified FE models. The key parameters affecting the buckling behaviors and ultimate strength were investigated, including the regularized slenderness ratio, eccentricity, width-thickness ratio (for SHS columns) and diameter-thickness ratio (for CHS columns). The ultimate strength obtained from the previous loading tests and the finite element analysis (FEA) were compared with the design strength predicted by the current Chinese (GB 50429), European (Eurocode 9), American (AA-2010) design codes for aluminum alloy structures. In addition, the newer proposed design method – the direct strength method (DSM), were also investigated. It was found that these four design provisions were generally conservative for predicting the ultimate strength of the SHS and CHS columns for 6082-T6 aluminum alloy and DSM was shown to provide more accurate strength predictions than the current design codes. Finally, the optimal distribution types of the model error (ME) in the four design provisions were investigated and reliability analysis was conducted under different load ratios to evaluate the safety levels of the three current design codes and DSM. Revised Chinses code was proposed to predict the ultimate strength of 6082-T6 aluminum alloy columns more precisely. Graphical abstract: Image 1 Highlights: A parametric study was performed to generate additional column buckling data. Design provisions of GB 50429, Eurocode 9, AA-2010 and DSM were introduced. The accuracy and reliability levels of the design provisions were assessed. Modification of the Chinese code was presented to apply 6082-T6 aluminum alloy.